Peran Guru Dalam Meningkatkan Perkembangan Sosial Anak Autis Usia Dini di SLB TNCC Banda Aceh - Yovi Apriliyani; Dhia Rahmadika; Sherina Wifda; Hijriati Hijriati (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Autistic children are children who experience growth and development disorders which have an impact on problems in optimal social, communication and emotional development. This research aims to ilustrate the role of teachers in improving the social skills of young autistic children at SLB TNCC Banda Aceh. The type of research used in this research is qualitative research. The subject of this research was an early-age autistic child who was in the Therapy class at TNCC SLB. Data collection techniques through observation and interviews. The results of the research show that there is a teacher's role as a facilitator, namely providing a platform for autistic children to improve the social development of autistic children at an early age through playing together as a form of interaction with friends around them at school. Teachers also provide stimulation that suits the needs of autistic children.